Individual differences in self-reported use of assessment feedback: the mediating role of feedback beliefs. Issue 7 (9th August 2021) - Winstone, Naomi E.; Hepper, Erica G.; Nash, Robert A.
Abstract: Feedback can rarely enhance learning unless it is used; however, few studies have examined individual differences in students' engagement with feedback. The present study explored (a) the extent to which personality variables and achievement goal orientation are associated with students' self-reported use of feedback; and (b) whether beliefs about feedback (utility, accountability, self-efficacy, and volition to implement feedback) mediate these associations. Students aged 16–18 ( N  = 746) completed self-report measures assessing each of these constructs. Self-reported feedback use was greater among students who scored high in mastery approach goals, performance approach goals, and conscientiousness. Controlling for academic achievement (which correlated weakly with self-reported feedback use), all of these associations were mediated by self-efficacy, and a subset of the associations were also mediated by the perceived utility of feedback and volition to implement feedback. Supporting students to feel competent in using feedback should be a key priority for interventions.